Analisis Kebutuhan Sistem Informasi Manajemen Kegiatan Kemahasiswaan STIKI Malang Menggunakan Agile Requirements Engineering - Nadya Rizky Ayyub Tam; Koko Wahyu Prasetyo; Bagus Kristomoyo Kristanto (LPPM STIKI MALANG, 2022)
Information technology plays a significant role in the governance of higher education institutions. Most of these institutions utilize integrated information system applications in the management decision-making processes. Student affairs is one of the strategic areas managed in higher education institutions. Student affairs area requires efficient data and information management related to the operations and management of student activities through the application of information systems. Meanwhile, agile development methodology can be used to develop information system applications that are responsive to user needs. By utilizing the Scrum framework that adopts the principles of agile methodology, this study presents a list of application requirements for student information systems in the product backlog and sprint backlog artifact formats. There are 31 product backlog items that have been identified through the results of user story analysis. The product backlog can then be implemented into application features for student affairs management information systems.